EP434 Survival of patients with early-stage cervical cancer after abdominal or laparoscopic radical hysterectomy in the Netherlands. (1st November 2019) - Wenzel, H; Smolders, R; Beltman, J; Lambrechts, S; Trum, H; Yigit, R; Zusterzeel, P; Zweemer, R; Bekkers, R; van der Aa, M
Abstract : Introduction/Background: In the previous decades, laparoscopic radical hysterectomy (LRH) has been introduced as alternative to abdominal radical hysterectomy (ARH) in early-stage cervical cancer. In 2018, results from the first prospective randomised study (the 'LACC' trial) were published, reporting inferior survival in patients treated with LRH. Therefore, we aimed to evaluate survival outcomes for patients treated with ARH and LRH for early-stage cervical cancer, in the Netherlands. Methodology: In this retrospective study, patients diagnosed between 2010 and 2017 with cervical cancer FIGO (2009) stage IA2 with lymphovascular space invasion, IB1 and IIA1, who underwent ARH or LRH, were identified from the Netherlands Cancer Registry. Weighted multivariable Cox regression with propensity score, based on Inverse Probability Treatment Weighting, was applied to examine the effect of ARH and LRH on overall survival (OS) and disease-free survival (DFS). Results: Of the 1107 patients, ARH was performed in 738 (67%) and LRH in 369 patients (of which 73% treated by robot surgery). Pathological lymph nodes were more often observed in the ARH group (18% vs. 8%), as were tumours ≥20 mm (62% vs. 36%), depth of invasion >10 mm (31% vs. 14%), surgical margin involvement (4% vs. 1%) and recurrences (13% vs. 7%). Patients with ARH also showed higher mortality (9% vs. 5%) and lower unadjusted 5-year OS (85% vs. 92%) and 5-year DFS (83% vs. 91%). However, weighted Cox regression analyses showed similar 5-year OS (95% vs. 95%) and 5-year DFS (89% vs. 89%) in both groups. Subanalyses on clinical tumour size showed similar 5-year OS (98% vs. 99%) and 5-year DFS (93% vs. 96%) for tumours <20 mm and similar 5-year OS (94% vs. 92%) and 5-year DFS (84% vs. 81%) for tumours ≥20 mm. Conclusion: Our observational data showed no difference in survival between ARH and LRH for early-stage cervical cancer, in the Netherlands. Disclosure: None of the authors received financial support for the research and/or authorship of this article. Hans Wenzel - Nothing to disclose; Ramon Smolders - Nothing to disclose; Jogchum Beltman - Nothing to disclose; Sandrina Lambrechts - Nothing to disclose; Hans Trum - Nothing to disclose; Refika Yigit - Nothing to disclose; Petra Zusterzeel - Nothing to disclose; Ronald Zweemer - Proctor Intuitive Surgical; Ruud Bekkers - Nothing to disclose; Maaike van der Aa - Nothing to disclose.